2020
DOI: 10.2147/ppa.s277367
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Health-Related Quality of Life in Women with Community-Acquired Urinary Tract Infections Using the EQ-5D-3L in Saudi Arabia</p>

Abstract: Purpose: Community-acquired urinary tract infection (CA-UTI) is a common and costly condition in females. Currently, there are no data on CA-UTI and quality of life (QoL) in Saudi Arabia. The aim of this study was to evaluate the impact of UTI and related sociodemographic characteristics on health-related quality of life (HRQoL) of Saudi females using the EuroQol 5-Dimension, 3-Level (EQ-5D-3L) instrument before and after treatment. Patients and Methods: This was a cross-sectional questionnaire study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…The most studied condition was diabetes mellitus (n=4), 23–26 followed by musculoskeletal disorders, back pain, and injuries (n=3). 27–29 The remaining articles focused either on a specific condition, such as urinary tract infections, 30 chronic obstructive pulmonary disease, 31 or multiple sclerosis; 32 on a treatment, such as teriparatide, 33 warfarin, or apixaban; 34 or on a nonspecific condition. 35 For all the reviewed studies, only one study reported the Cronbach’s alpha value of 0.72, which could indicate an acceptable reliability and an opportunity for enhancement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studied condition was diabetes mellitus (n=4), 23–26 followed by musculoskeletal disorders, back pain, and injuries (n=3). 27–29 The remaining articles focused either on a specific condition, such as urinary tract infections, 30 chronic obstructive pulmonary disease, 31 or multiple sclerosis; 32 on a treatment, such as teriparatide, 33 warfarin, or apixaban; 34 or on a nonspecific condition. 35 For all the reviewed studies, only one study reported the Cronbach’s alpha value of 0.72, which could indicate an acceptable reliability and an opportunity for enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…Only three of the thirteen official administrative Saudi Arabian regions have been studied: Riyadh, 26 , 29 , 30 , 34 Makkah, 24 , 27 , 32 and Dammam. 23 Riyadh likely accounts for more publications, being the capital of the KSA and home to many hospitals and universities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean baseline HRQoL of Saudi women with UTI was 72% with varying effects depending on the socio-demographic characteristics and other comorbid chronic diseases. 2,10,11 The mean cost for UTI treatment in EDs in Saudi Arabia is estimated as $134.56 ± $31.34 (United States [US] dollars). 2 UTI is among the most common reasons for outpatient visits and antibiotic use in adult populations.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive and inappropriate antibiotic use can have a negative impact, including treatment failure, antibiotic resistance, risk of complications, and increased cost of treatment, on patients and society. 1,2,7,11,12,[14][15][16] The increasing prevalence of antibacterial resistance among community uro-pathogens affects the diagnosis and management of this clinical syndrome. 3,6 The challenges of managing UTIs in an ED include limited medical history, lack of follow-up, and lack of culture and susceptibility results.…”
Section: Introductionmentioning
confidence: 99%